Red Chili Farming on Coastal Sand Land with Shower Irrigation System: A Review of Production Efficiency - Risvansuna Fivintari Francy; Shofiyah Anis (E3S Web of Conferences)
Farming on marginal land, one of which is coastal land, requires its own efforts because it is quite a big challenge. The characteristics of marginal land are minimal nutrients, porous soil type, and quite extreme weather because it is located on the coast. This condition needs to be addressed. One alternative to overcome the problem is to provide large amounts of fertilizer and sufficient irrigation. The irrigation system is an important thing to address the water needs of the land. The use of large amounts of fertilizer must still be adjusted to the needs of red chili plants on coastal land, so that it does not have a negative impact on production and inefficient use. So, this research aims to determine the factors that influence production and determine the efficiency of using production factors in red chili farming with an irrigation system. shower on beach sand land in Panjatan District. The research sample was determined using the census method with a total of 50 farmers. Data was analyzed using a type of production function model Cobb-Douglass and then analyzed the level of efficiency. The results of the research analysis show that production factors influence red chili production using an irrigation system shower on coastal sand land are land area, liquid insecticide and solid fungicide. The use of land area production factors and liquid insecticides is at an efficient level.